The Role of Majority Status in Shaping Self-Esteem: A Comparative Study of Muslim and Christian College Students in Indonesia - Aditya, Yonathan; Martoyo, Ihan; Nurcahyo, Firmanto Adi; Buana, Dana Riksa (European Journal of Mental Health, 2025)
Introduction: Self-esteem is an adaptive trait that boosts well-being. The relationship between religiosity and self-esteem is complex, with mixed results from empirical studies. Culture and dimensions of religiousness may influence this relationship. Aim: The main purpose of this study is to understand the connection between religiousness and self-esteem in two different conditions: as a majority and as a minority. Methods: This study’s participants are college students who identify as Muslim or Christian. They are from two regions in Indonesia: Jabodetabek (Java Island), where Muslims are the majority; and East Nusa Tenggara and North Sulawesi (outside of Java), where Muslims are in the minority. Most of the respondents were between 18 and 25 years old. The survey was conducted online. Results: No significant differences emerged in religiousness and self-esteem between Muslims and Christians in both Java and regions outside of Java. However, students outside Java Island exhibited higher religiousness and self-esteem, irrespective of their religious affiliation. Conclusion: This study indicated that religiosity is a social value, with some exceptions.